Design and Impact Analysis of a Grid-Connected Solar Photovoltaic System in Ibri, Oman - Mehmood, Arshad; Al Kalbani, Waleed Saif Abdullah Habib (Nature environment and pollution technology, 2025)
This study investigates the feasibility of establishing a grid-connected power system in Ibri, Oman. The primary goal is to address the rising energy demands and contribute to fighting climate change. By leveraging Ibri’s resources, the research highlights the feasibility of such a system, focusing on its economic, technological, and environmental benefits. Using PVsyst software for planning and evaluation, the study assesses climate conditions, component choices, and performance predictions to ensure optimal system performance. The proposed 10.81 kWp solar power system estimates an energy production of 16,981 kWh, achieving a system efficiency of 67.2% based on the performance ratio (PR). The financial analysis estimates a payback period of 7.5 to 8.3 years, with an internal rate of return (IRR) of 11.15% and a net present value (NPV) of $32,024.28, confirming the project’s viability. The system is expected to reduce carbon emissions by 379.939 tons over its lifetime, highlighting the significant ecological benefits of adopting solar energy (SE). The research demonstrates that incorporating PV systems in regions like Ibri is technically viable, economically beneficial, and environmentally advantageous. This study is a valuable resource for energy initiatives, promoting sustainable power production methods and encouraging the broader adoption of renewable technologies for a sustainable future.